Pemberdayaan Keluarga Melalui Kewiraswastaan - Farah Chalida Hanoum; Ria Kusumaningrum (Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
The field of entrepreneurship and family business consist of separate and distinct but overlapping domains. The intersection of the two domains provides a uniqe perspective from which to examine six strategic management issues : leadership, culture, board of directors, life cycles, strategic management process, ethics and values.